CREATIVE ACTIVITY OF STUDENTS IN MOTHER LANGUAGE TEACHING METHODOLOGY LESSONS IMPORTANCE OF DEVELOPMENT - Adizova Nodira (Zeta Repository, 2023)
The article talks about the fact that today the field of education in Uzbekistan has become an area of significant innovative changes, and the quality of education in our country is rising to a high level. If, on the basis of such changes, non-standard approaches are widely used in the educational process, the introduction of problematic educational technologies into the educational process by maintaining its fundamental, continuity and integrity at all levels of education is expressed as one of the urgent problems.